Nueva especie del quitón Lepidochitona(Polyplacophora: Ischnochitonidae) de Puerto Rico - I. García-Ríos, Cedar (Revista de Biología Tropical, 2010)
The genus Lepidochitona Gray, 1821 has two species in the Caribbean: L. liozonis (Dall & Simpson, 1901) and L. rosea Kaas, 1972. We describe a third species: Lepidochitona rufoi sp. nov. from Puerto Rico. Lepidochitona rufoi differs from both in having a finely granulose tegmentum, smaller size, a very fine central radula tooth, and different anal plate form and color pattern. It also differs from L. liozonis in having longer marginal spicules.